2008
DOI: 10.1209/0295-5075/81/64002
|View full text |Cite
|
Sign up to set email alerts
|

Time scales separation for dynamo action

Abstract: Abstract. -The study of dynamo action in astrophysical objects classically involves two timescales: the slow diffusive one and the fast advective one. We investigate the possibility of field amplification on an intermediate timescale associated with time dependent modulations of the flow. We consider a simple steady configuration for which dynamo action is not realised. We study the effect of time dependent perturbations of the flow. We show that some vanishing low frequency perturbations can yield exponential… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…A similar behavior has also been found previously in an ideal two-dimensional model by the authors of Ref. [26], who examined the induction action of a uniform shear flow perturbed by an periodic variation on intermediate time scales. The authors found a perpetual amplification even for very small perturbation amplitudes and concluded that tiny distortions ∼ Rm −1 can be sufficient to alter the ability of a flow to provide for dynamo action.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…A similar behavior has also been found previously in an ideal two-dimensional model by the authors of Ref. [26], who examined the induction action of a uniform shear flow perturbed by an periodic variation on intermediate time scales. The authors found a perpetual amplification even for very small perturbation amplitudes and concluded that tiny distortions ∼ Rm −1 can be sufficient to alter the ability of a flow to provide for dynamo action.…”
Section: Introductionsupporting
confidence: 83%
“…The exclusive occurrence of dynamo action with a time-dependent flow was interpreted as dynamo action based on non-normal growth originally described in Refs. [26,27]. Looking at the details, a number of differences become visible between the study of Ref.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that the magnetic mode amplified by the mean flow can be strongly inhibited by turbulent fluctuations that favour another magnetic mode at the dynamo threshold. However, we also know examples of dynamos generated by a time-dependent velocity field whereas the same velocity field frozen at any particular time is not a dynamo (Dormy & Gerard-Varet 2008; Tilgner 2008). Finally, in the context of mean-field magnetohydrodynamics, examples of dynamos generated only by fluctuations without any mean velocity are well known.…”
Section: Effect Of Fluctuations On the Dynamo Thresholdmentioning
confidence: 99%
“…This scaling, Pm c ∼ E 3/4 , has, as far a we are aware, not yet been interpreted. We propose here an interpretation in term of exponential amplification by a time dependent shear (Dormy and Gérard-Varet [24]). We know (Morin [25], Morin and Dormy, in preparation) that the minimum value of Pm for dynamo action does not correspond to an instability of the hydrodynamic solution to a magnetic perturbation, but instead to a detached dynamo branch.…”
Section: Direct Numerical Simulationsmentioning
confidence: 99%
“…These scalings are all expressed using the viscous timescale as unit of time. Following Dormy and Gérard-Varet [24], we note that dynamo action through a rotating shear requires τ β < τ η (where τ η = L 2 /η and τ β is the typical timescale of rotation or oscillation of the shear, here a rotation). We then get (with this unit of time) the necessary condition for this dynamo mechanism (based on timescale separation) to occur, Pm > E 2/3 (because Pm measures τ η in the τ ν timescale).…”
Section: Direct Numerical Simulationsmentioning
confidence: 99%